Effect of temperature on gas production from hydrate-bearing sediments by using a large 196-L reactor. (1st September 2020) - Wang, Yun-Fei; Wang, Ling-Ban; Li, Yang; Gu, Jin-Xiang; Sun, Chang-Yu; Chen, Guang-Jin; Wang, Xiao-Hui; Yuan, Qing; Li, Nan
Highlights: Hydrate depressurization exploitation for reservoir with a gas-rich zone was simulated. Gas production efficiency of single well and double well was compared. Continuous depressurization can prevent well plugging caused by excessive pressure drop. Hydrate decomposition rate was accelerated when exploitation below the freezing point. Heat released from ice formation and salt precipitation promote hydrate decomposition. Abstract: Methane hydrate exploitation via depressurization for a reservoir with a bottom gas-rich zone was simulated using a large-sized three-dimensional hydrate simulator. A single vertical well system and a system with a combination of vertical and horizontal wells were employed to elucidate the different effects of horizontal and vertical wells on the exploitation process. The results showed that effect of promoting gas production using a horizontal well is not obvious for a high permeability reservoir. A large exploitation temperature drop may lead to ice blockage in the pipelines, and fracturing technology was introduced to solve this blockage problem. Experiments performed above and below the freezing point inferred that the decomposition of the hydrate in different areas of the reactor was not simultaneous, according to analysis of the temperature distribution of the entire reactor during the exploitation process. For exploitation above the freezing point, temperatures in the bottom of the reactor tend to maintain a low level and work against hydrate decomposition. However, for exploitation below the freezing point, the low-temperature area in the bottom of the reactor preferentially converts to ice. Heat release and salt precipitation promoted hydrate decomposition, and the decomposition rate was significantly accelerated.